Petrographic Characterization and Maceral Controls on Porosity in Overmature Marine Shales: Examples from Ordovician-Silurian Shales in China and the U.S. - Lin Wei; Shasha Sun; Dazhong Dong; Zhensheng Shi; Jia Yin; Shudi Zhang; Maria Mastalerz; Xiong Cheng (Geofluids)
The pore structure characterization and its controlling factors in overmature shales are keys to understand the shale gas accumulation mechanism. Organic matter in source rocks is a mixture of various macerals that have their own specific evolutionary pathways during thermal maturation. Pores within macerals also evolve following their own path. This study focused on petrographic characterization and maceral controls on porosity in overmature marine shales in China and the United States. Shale from Ordos Basin in China was also selected as an example of overmature transitional shale for maceral comparison. Organic petrology techniques were used to identify maceral types and describe morphological features in detail; scanning electron microscopy techniques were then used to document the abundance and development of pores within macerals. Helium measurement, mercury intrusion capillary pressure, and CO2 adsorption were especially applied to quantify the pore structure of Wufeng-Longmaxi shale from Sichuan Basin in China. The vitrinite reflectance equivalent of the studied overmature samples is ~2.4%. The macerals within the studied marine shales are composed mainly of pyrobitumen and zooclasts. At this maturity, pyrobitumen develops abundant gas-related pores, and their volume positively correlates to gas content. Three types of pyrobitumen and its related pore structure are characterized in Wufeng-Longmaxi shales. Zooclasts contribute to total organic carbon (TOC) content but little to porosity. When the TOC content is above 1.51% in Wufeng-Longmaxi samples, the TOC content positively correlates to quartz content. Organic matter strongly controls micropore development. Pores of diameter~0.5 nm provide a significant amount of micropore volume. Clay mineral and quartz contents control micro- and macropore increments in organic-lean shales. MICP results indicate that pores within 3-12 nm and 900-2500 nm account for a major contribution to pore volume obtained. Determining the proportions of pyrobitumen to zooclasts within the total organic matter in pre-Devonian organic-rich marine shales is important in predicting porosity and gas storage capacity in high-maturity shales.